Challenges in Conducting Sexual Health and Violence Research in Older Adults Beyond the General Data Protection Regulation: A Belgian Case Study - Nobels, Anne (Journal of interpersonal violence, 2022)
Because of a growing older population, the sexual health (SH) of older adults, including sexual violence (SV), is becoming an increasingly important public health concern. Yet, reliable SV prevalence rates and risk factors are lacking, due to methodological shortcomings in current studies. SV research involves challenges regarding safety and disclosure, especially in older adults. In this paper, we reflect on the methods used in a sexual health and violence (SH&V) study in older adults balancing between privacy rules imposed by the General Data Protection Regulation (GDPR) and ethical and safety guidelines.To ensure the acceptability of the questionnaire, it was tested in a two-phase pilot study. To maximize SV disclosure, the questionnaire built up gradually towards the more sensitive SV modules. Interviewers were trained to approach participants in a non-judgmental manner. Due to GDPR, our data collection method was changed from a random sampling via the National Register to a cluster random probability sampling with a random walk finding approach.Older adults were willing to discuss SH&V during a structured face-to-face interview with trained interviewers. Following strict safety guidelines, no major incidents were reported. The cluster random probability sampling with random walk finding approach provided an adequate sampling frame, but was inefficient and time-consuming.Doing research on SH&V in older adults is feasible but requires a substantial investment of time and the challenges involved may incur greater costs. In order to guarantee further research on sensitive topics in older adults, we recommend that an interdisciplinary expert group consisting of researchers, donors, and policymakers investigates how GDPR and public health research in hard-to-reach populations can be better matched.